Perception of Indian medical students regarding introduction of early clinical exposure - Kalpesh Vidja; Jitendra Patel; Jasmin Parmar; Pratik Akhani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The Medical Council of India (MCI) has stressed the necessity of Early Clinical Exposure (ECE) for a better understanding of preclinical medical subjects. However, its implementation at the medical college level in the current Indian scenario is a big challenge due to the large classroom strength and smaller number of faculty in preclinical subjects. The aim of this study to introduce ECE in physiology at our medical college, we planned an ECE session on anaemia and recorded the students' perceptions regarding the same. We conducted an ECE session on Anemia designed by the subject experts of the Physiology and Medical Education Unit (MEU) faculty of our institute. We conducted a cross-sectional survey among MBBS students of 2019 batch using a pre-validated questionnaire via online Google form to capture their perceptions regarding the ECE session. After exclusion, a total of 127 responses from medical students were included for data analysis. The majority of the students responded that the overall format of the ECE session was appropriate and that the session was helpful to them in the clinical application of their knowledge about Anemia. More than 75% of students opined that the ECE session made basic science learning more interesting and they felt motivated to read further on the topic. About 80% of students preferred ECE over traditional teaching. In conclusion, Students find ECE to be interesting, motivating, and helpful for the clinical application of basic science knowledge into clinical practice. Hence, ECE should be conducted more frequently and more topics should be taught by ECE at all medical colleges.